Review on phytochemical constituents and pharmacological activities of genus Galium - Mayssaloune Ali Kanso, Mohamed Ali Hijazi, Abdalla El-Lakany, Maha Aboul-Ela (Journal of Applied Pharmaceutical Science, 2024)
Medicinal plants are a rich source of phytochemical constituents of diverse structures that are behind their various pharmacological effects. Plants of genus Galium named Bedstraws, family Rubiaceae, are distributed throughout North and South America, Europe, the northern U.S., southern Canada, and tropical Asia. More than 600 species have been used in traditional medicine for treating different ailments. Owing to the valuable published uses of these plant species, and the versatility of their bioactive metabolites such as Galium verum, Galium aparine, Galium mollugo, and G. odoratum, it was deemed interesting to summarize the previous studies done on this genus to discuss the pharmacological profile of all isolated classes of metabolites. The search was adopted using some essential keywords such as Galium, phytochemistry, pharmacology, and biological activity from journals and books in databases such as Scopus, Elton B. Stephens CO, ScienceDirect, Embase, security identifier, and Medline from 1995 to 2024. The results showed that species belonging to Galium have various pharmacological activities including antimicrobial, antioxidant, anti-cancer, immunomodulatory, and anti-inflammatory effects because they are rich in phenolic compounds, iridoid glycosides, anthraquinones, phytosterols, saponins, and essential oils. Accordingly, this review will stimulate the scientific community for further research and boost the discovery of novel bioactive compounds from various species belonging to this genus distributed worldwide.
Keywords: Galium, Rubiaceae, phytochemistry, pharmacology, biological activity